Potential Implications of Hyperoside on Oxidative Stress-Induced Human Diseases: A Comprehensive Review - Wang K; Zhang H; Yuan L; Li X; Cai Y (Dove Medical Press, 2023)
Kaiyang Wang,1,* Huhai Zhang,2,* Lie Yuan,3,4 Xiaoli Li,3,4 Yongqing Cai1 1Department of Pharmacy, Daping Hospital, Army Medical University, Chongqing, People's Republic of China; 2Department of Nephrology, Southwest Hospital, Army Medical University, Chongqing, People's Republic of China; 3Department of Pharmacology, College of Pharmacy, Chongqing Medical University, Chongqing, People's Republic of China; 4Chongqing Key Research Laboratory for Drug Metabolism, College of Pharmacy, Chongqing Medical University, Chongqing, People's Republic of China*These authors contributed equally to this workCorrespondence: Yongqing Cai, Department of Pharmacy, Daping Hospital, Army Medical University, No. 10 Changjiang Branch Road, Yuzhong District, Chongqing, 400042, People's Republic of China, Tel +86 023 68746950, Email cy0721@163.com Xiaoli Li, Department of Pharmacology, College of Pharmacy, Chongqing Medical University, No. 1 Yixueyuan Road, Yuzhong District, Chongqing, 400016, People's Republic of China, Tel +86 023 63657050, Email lixiaoli@cqmu.edu.cnAbstract: Hyperoside is a flavonol glycoside mainly found in plants of the genera Hypericum and Crataegus, and also detected in many plant species such as Abelmoschus manihot, Ribes nigrum, Rosa rugosa, Agrostis stolonifera, Apocynum venetum and Nelumbo nucifera. This compound exhibits a multitude of biological functions including anti-inflammatory, antidepressant, antioxidative, vascular protective effects and neuroprotective effects, etc. This review summarizes the quantification, original plant, chemical structure and property, structure-activity relationship, pharmacologic effect, pharmacokinetics, toxicity and clinical application of hyperoside, which will be significant for the exploitation for new drug and full utilization of this compound.Keywords: hyperoside, original plant, chemical structure, pharmacology, pharmacokinetics, toxicity